Pencantuman Aliran Kepercayaan dalam Kolom Agama Pada Kartu Tanda Penduduk (Analisis Kasus pada Putusan Mahkamah Konstitusi No. 97/PUU-XIV/2016) - Samhudi, Gamalel Rifqi (Kosmik Hukum, 2022)
Abstract All elements contained in the contents of the Identity Card (KTP) are things that are filled in according to the provisions of the Owner's Identity, including the urgency of filling in the religious column which must be filled in according to the beliefs of the owners of the KTP. The issuance of Law Number 23 of 2006 concerning Population Administration, among others, mandates the development of a national population administration system. The development of this system is important because it not only has a significant effect on the government's agenda in optimally providing public services. With this law, population administration as a system is expected to be implemented as part of the administration of state administration. The existence of Article 61 paragraph (1) and paragraph (2) in conjunction with Article 64 paragraph (1) and (5) of the Population Administration Law violates the human rights of believers and applicants as citizens. Because Article 61 paragraph (2) of the Population Administration Law states that information regarding the religion column on the family card for residents whose religion has not been recognized as a religion based on the provisions of laws and regulations or for believers in beliefs is not filled in, but is still served and recorded in the database. population. Furthermore, Article 64 paragraph (2) of the Population Administration Law states that information about religion in Electronic Identity Cards (E-KTP) for Residents whose religion has not been recognized as religion based on the provisions of laws and regulations or for believers in beliefs is not filled in, but is still served and recorded in the population database. These two articles have the potential to eliminate the right of citizens to obtain a Family Card (KK) and an electronic Identity Card (KTP), even though in the a quo law article it is stated that they will still be served and recorded in the population database. Keywords: Identity Card, Religion and Belief, Citizen's Human Rights. Abstrak Semua elemen yang terdapat dalam isi Kartu Tanda Penduduk (KTP) merupakan hal yang diisi sesuai ketentuan dengan Identitas Pemilik, termasuk urgensi pengisian kolom agama yang harus diisi sesuai dengan keyakinan para pemilik KTP. Diterbitkannya Undang-undang Nomor 23 Tahun 2006 tentang Administrasi Kependudukan, antara lain mengamanatkan pembangunan sistem administrasi kependudukan secara nasional. Pembangunan sistem ini adalah hal penting karena tidak saja berpengaruh secara signifikan terhadap agenda pemerintah dalam pelayanan publik secara optimal. Dengan undang-undang tersebut, maka administrasi kependudukan sebagai suatu sistem diharapkan dapat diselenggarakan sebagai bagian dari penyelenggaraan administrasi negara. Keberadaan Pasal 61 ayat (1) dan ayat (2) jo Pasal 64 ayat (1) dan (5) Undang-undang Administrasi Kependudukan melanggar hak asasi penghayat kepercayaan dan pemohon selaku warga negara. Karena dalam Pasal 61 ayat (2) Undang-undang Administrasi Kependudukan menyatakan bahwa keterangan mengenai kolom agama pada kartu keluarga bagi penduduk yang agamanya belum diakui sebagai agama berdasarkan ketentuan peraturan perundang-undangan atau bagi penghayat kepercayaan tidak diisi, tetapi tetap dilayani dan dicatat dalam database kependudukan. Selanjutnya Pasal 64 ayat (2) Undang-undang Administrasi Kependudukan menyatakan bahwa keterangan tentang agama dalam KTP Elektronik bagi Penduduk yang agamanya belum diakui sebagai agama berdasarkan ketentuan peraturan perundang-undangan atau bagi penghayat kepercayaan tidak diisi, tetapi tetap dilayani dan dicatat dalam data base kependudukan. Kedua pasal ini berpotensi menghilangkan hak warga negara untuk mendapatkan Kartu Keluarga (KK) dan KTP elektronik, meskipun dalam pasal undang-undang a quo disebutkan tetap dilayani dan dicatat dalam database kependudukan. Kata kunci: Kartu Tanda Penduduk, Agama dan Keyakinan, Hak Asasi Warga Negara